2016
DOI: 10.1093/nar/gkw657
|View full text |Cite
|
Sign up to set email alerts
|

eIF2β is critical for eIF5-mediated GDP-dissociation inhibitor activity and translational control

Abstract: In protein synthesis translation factor eIF2 binds initiator tRNA to ribosomes and facilitates start codon selection. eIF2 GDP/GTP status is regulated by eIF5 (GAP and GDI functions) and eIF2B (GEF and GDF activities), while eIF2α phosphorylation in response to diverse signals is a major point of translational control. Here we characterize a growth suppressor mutation in eIF2β that prevents eIF5 GDI and alters cellular responses to reduced eIF2B activity, including control of GCN4 translation. By monitoring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 68 publications
3
16
0
Order By: Relevance
“…Because EIF-2c(S443L) can functionally substitute for the eIF2Bg subunit, but not for eIF2Be ( Figure 2B), the alternative mechanism underlying eIF2(aP) resistance is likely to involve a molecular event catalyzed exclusively or predominantly by eIF2Bg, which is not the GTP-GDP exchange that is largely mediated by eIF2Be (Pavitt et al 1998). The eIF2Bg subunit has been shown to also participate in the displacement of the translational regulatory factor eIF5 that prevents GDP dissociation from the translation-incompetent eIF2-GDP complex, thus antagonizing the exchange activity of eIF2B required for translation initiation (Jennings et al 2016). It is plausible that the S443L change in eIF2g facilitates the displacement of eIF5, bypassing the requirement for eIF2Bg in dissociating eIF5 from eIF2 to promote translation-competent eIF2 complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…Because EIF-2c(S443L) can functionally substitute for the eIF2Bg subunit, but not for eIF2Be ( Figure 2B), the alternative mechanism underlying eIF2(aP) resistance is likely to involve a molecular event catalyzed exclusively or predominantly by eIF2Bg, which is not the GTP-GDP exchange that is largely mediated by eIF2Be (Pavitt et al 1998). The eIF2Bg subunit has been shown to also participate in the displacement of the translational regulatory factor eIF5 that prevents GDP dissociation from the translation-incompetent eIF2-GDP complex, thus antagonizing the exchange activity of eIF2B required for translation initiation (Jennings et al 2016). It is plausible that the S443L change in eIF2g facilitates the displacement of eIF5, bypassing the requirement for eIF2Bg in dissociating eIF5 from eIF2 to promote translation-competent eIF2 complex formation.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time the competition for eIF2 between eIF2B and Met-tRNA i Met is also influenced by the competition for eIF2 between eIF2B ε-cat and eIF5-CTD 56, 43, 57 , which share the same fold. Both eIF2B ε-cat and eIF5-CTD bind the eIF2γ-G domain as well as the same region in eIF2β 56, 43, 57 , the former displacing the nucleotide and the latter protecting it from displacement 58, 53,59 . While eIF2B was shown to disrupt TC 53 , however adding eIF5 or eIF5-CTD to the TC protected it from disruption, but not when eIF2α is phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…1, includes the pathway (termed as route 2) for the regeneration of eIF2:GDP due to intermediate complex constituting factors eIF2B and eIF5 [5]. The formation of eIF2:GDP:eIF2B GEF complex can either occur via release of eIF5 prior to the recruitment of eIF2B (termed as route 1), or through eIF2:GDP:eIF5:eIF2B intermediate complex [19], [20]. In the recent study, it has been found that eIF2B functions as an activator of eIF5 dissociation from eIF2:GDP:eIF5 complex, indicates that out of the two routes, latter route is preferred for the regeneration of eIF2:GDP [19], [20].…”
Section: Methodsmentioning
confidence: 99%
“…where, ξ 1 is an absolute error between in vitro and simulated experimental values, Y 1D is the in vitro experimental data value for haploid yeast cell, C j is the set of rate constant and Y 1 (Y i (0), C j , t) is the simulated experimental value of protein obtained by solving ODEs for Y i (0) and C j initial conditions, and j ∈ [1,20]. Note that, out of 10 5 random experiments, the percentage of parameter combinations giving ξ 1 ≡ 0 is 1.684%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation